The Effectiveness Of M-Puzzle Toward Preschooler Spatial Skill - Wulan Patria Saroinsong; Faridah Ummu Imara; Nurhenti Dorlina Simatupang; Eka Cahya Maulidiyah (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2021)
This study aimed to determine the effectiveness of digital-based geometry puzzle games to stimulate the spatial intelligence of children aged 4-5 years. This type of research is RD (Research and Development) using the ASSURE model. This study used the target participants aged 4-5 years in PGRI II Taji Kindergarten as a test of instrument validity, Dharma Wanita Duriwetan Kindergarten as the main sample for testing a digital-based geometry puzzle product and NU Hidayatul Athfal Muslimat Kindergarten as a conventional product trial (LKA). The results showed that the digital- based geometric puzzle media that had been developed was more effectively used as a learning medium to stimulate children's spatial intelligence in recognizing shapes and colors compared to conventional media.